Simultaneous transformations of view and place coding across reference frames in the macaque brain - Yan Huang; Anran Liu; Xiao Xu; Kechen Du; Dun Mao (Proceedings of the National Academy of Sciences, 2026)
Vision enables primates to remotely map their environment using eye movements rather than physical locomotion. While view-related spatial coding is prevalent in the primate hippocampus, its origin and precise relationship to standard place coding remain largely unknown. Leveraging untethered neural recording, motion capture, and wireless eye tracking, we examined view and place coding along the parietal–retrosplenial–hippocampal pathway in macaque monkeys freely exploring an open arena. We identified opposing gradients of egocentric and allocentric spatial coding across this pathway. Acting as a critical intermediate hub, the retrosplenial cortex conjunctively encoded egocentric position and allocentric gaze direction through gain modulation. Further downstream, the hippocampus exhibited both direction-dependent and direction-invariant place coding. Notably, view responses were much more prevalent than this place selectivity and were distinctly driven and modulated by shifting gaze directions. Ultimately, our findings establish that view and place coding actively coexist to varying degrees within the primate hippocampus. These results further reveal that such complex view representations emerge from the integration of distinct spatial reference frames within the retrosplenial cortex.